Monday

April 21, 2014

April 21, 2014

Posted by **Shay** on Wednesday, January 17, 2007 at 7:45pm.

y=3x^2-6x by factoring

y = 3x^2 - 6x

Factor out 3x:

y = 3x(x - 2)

Set each factor equal to 0:

3x = 0; x = 0

x - 2 = 0; x = 2

Those are your x-intercepts.

I hope this will help.

**Related Questions**

Math - How to rewrite an expression with negative exponents such as : -12(3x-1...

Algebra - I'm not sure how to factor 3x^3-12x^2+3x. I tried separatring the 3x ...

math,help - Is this trinomial a perfect square x^2-6x+9 if the trinomial starts ...

calculus - I am trying to find equation of the tangent line to the curve 2/(1-3x...

math - 3x-4=-2(3x+5) 3x-4=-2(3x+5) clear the fraction. 3x-4=-6x-10 add+6x+4 to ...

algebra - simplify (6x^3-16x^2+11x-5)/(3x-2) (3x-2)(2x-1)^2-3 my muliple choice ...

math - simplify (x^2-3x+6)-(36x^2-18x+6/6) (x^2-3x+6)-(6(6x^2-3x+1/6) cancel the...

Math - Can you factor these for me? 12x^3 + 6x^2 - 3x - 2 2x^2 +x - 6 25 - 4(x^2...

Algebra - checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4...

BobPursley..here it is: - Problem 1: (x-2)/(3x+4) - 6x/(x+1) What I did: Common ...